Unlocking Performance: Person-Organization Fit and Job Satisfaction: Membuka Kinerja: Kecocokan Orang-Organisasi dan Kepuasan Kerja - Robbie, R. Iqbal; Majid, Nur Kholis; Novianti, Khusnul Rofida (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2024)
This quantitative study looks at the impact of person-organization fit on employee performance, including work happiness as an intervening variable, at PT. Victory International Futures. Using a saturation sampling strategy, the complete population of 150 employees was questioned via questionnaires. The data was analyzed using Smart PLS. The results show that person-organization fit has a strong positive effect on job satisfaction and employee performance. Furthermore, job happiness was proven to have a considerable impact on employee performance. The findings highlight the relevance of person-organization fit in improving employee performance, with job happiness serving as a key intermediary mechanism. This study contributes to the academic literature by filling gaps in our understanding of the relationship between person-organization fit, job satisfaction, and employee performance, thereby enhancing theoretical frameworks and providing insights for organizational practice.